Safety at work and current legal framework for the transport sector in anglophone Cameroon - Encho, Quinta Ewoh; Ab Rahman, Rozanah; Md Tamrin, Shamsul Bahri; How, Vivien (Human Factors and Ergonomics Society Malaysia, 2017)
Occupational Safety and Health is somewhat existing and on the rise issue in Cameroon. Like most developing countries, little or nothing is being done to stop the ever-increasing rate of accidents and injuries occurred at work. In the transport sector, the rate of occupational accidents and injuries in Cameroon is nothing to ride home about. Every day, thousands of people lost their lives. What is also more disturbing is the fact that when it comes to public transportation companies, the workers are not the only ones involved; the customers or passengers are too. The human cost of poor occupational safety and health is huge. This article discusses the adequacy of the current legal framework in the transport sector in Anglophone Cameroon and proposes a strategic driver towards achieving a safe place of work for this industry.